The relationship between job burnout, work values and organizational citizenship behaviours in Human Capital Management Departments (Petronas) / Nur Hazwani Ibrahim - Ibrahim, Nur Hazwani (2014)
This study conducted to identify the relationship between job burnout, work values and organizational citizenship behaviour. The researcher have chosen PETRONAS, Human Capital Management departments, to represent this study. Researcher have listed six variables which are emotional exhaustion, cynicism, reduced professional efficacy, intrinsic work values, extrinsic work values and organizational citizenship behaviour (OCBs). The sample for this study approximately 130 employees from different level and this survey are opened to all level of employee from this department to become the respondent. This will show the predictors that encouraging organizational citizenship behaviours OCBs in their organization from different level of employee. This study discussed the relationship that contributed towards OCBs and those factors will be the outcomes of this study. The finding and analysis were made based on Statistical Package for Social Science (SPSS) version 2.0 to analyse the data. The finding of this study proves that intrinsic work values, and extrinsic work values are significantly and positively related organizational citizenship behaviour and hypothesis are supported. Meanwhile emotional exhaustion and cynicism are significantly and negatively relationship and hypothesis also been accepted. However, for reduced professional efficacy the result show significantly and positively affected organizational citizenship behaviour, thus it is not supported. This might be because of different job level and industry compared to previous study.